Factors Influencing the Performance of Nurses-Midwives at Labor Wards: A Case Study of Three Regional Referral Hospitals, in Dar es Salaam (Tanzania Medical Journal, 2022)
BackgroundNursing and midwifery professions can transform the way health actions are organized and how health care is delivered if they are regulated and well supported. Despite rising global attention on health care delivery systems strengthening; there is a scarcity of information on the nurse-midwives’ performance specifically in the labor wards. The study aimed to assess nurse-midwives’ performance working in the labor wards.MethodsA qualitative case study design that applied in-depth interviews (IDIs) using a semi-structured interview guide conducted between May and June, 2017 in Dar es Salaam City. A purposive sample of 22 nurse-midwives working in labor wards in Amana, Mwananyamala and Temeke regional referral hospitals were recruited. IDIs were recorded by audiotape, then transcribed verbatim and analyzed using deductive content analysis. ResultsSeven sub-categories emerged from the data. The findings were presented into two categories: based on barriers for nurse-midwives’ performance include poor working environment, inadequate staffing level, insufficient medical supplies and equipment, and increased workload. The second category included facilitators for nurse-midwives’ performance such as Continuous Professional Development (CPD), leadership characteristics and supportive supervision.Conclusion and RecommendationsThe findings indicated interrelated factors influencing nurse-midwives’ performance. These factors go beyond the nurse-midwives’ desirability to provide high quality services; and cut across at different levels, these may underlie their inability to meet the required standards. The health care managers should support and motivate nurse-midwives to improve their performance. This could be done through provision of adequate medical supplies and equipment necessary for service execution, financial (allowances) for extra duty and non-financial incentives (on job training/seminars), and regular supportive supervision. Further studies among nurses, other health workers and health care managers may be crucial for improvement of maternal health care services.